2010
DOI: 10.1186/1471-230x-10-58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mannoprotein E1 in liquid diet on inflammatory response and TLR5 expression in the gut of rats infected by Salmonella typhimurium

Abstract: BackgroundMannoproteins are yeast cell wall componend, and rich in mannose. The use of foods rich in mannose as carbohydrate, could have a bioprotective effect against entrobacteria intestinal infection. Nothing is known about mannoproteins' activity in inflammatory bowel processes induced by entrobacteria.This study investigates the effects of mannoprotein administration via a liquid diet on inflammatory response and TLR5 expression during intestinal tissue injury in a rat model of infection with Salmonella t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…However, a tendency for lower IL-6 and TNF-α in serum was also verified for dogs fed the YCW diet, which did not alter SCFA fecal concentration. These data corroborate findings of other researchers [75], which evaluated the action of a yeast cell wall fraction called "mannoprotein", added to a liquid diet for rats with Salmonella infection. The authors also found lower expression of TNF-α and IL-6 mRNA in the jejunum, ileum and colon tissues in the treatment groups and concluded that yeast cell wall derivates may lower the inflammatory response, protecting the intestinal tissue.…”
Section: Discussionsupporting
confidence: 91%
“…However, a tendency for lower IL-6 and TNF-α in serum was also verified for dogs fed the YCW diet, which did not alter SCFA fecal concentration. These data corroborate findings of other researchers [75], which evaluated the action of a yeast cell wall fraction called "mannoprotein", added to a liquid diet for rats with Salmonella infection. The authors also found lower expression of TNF-α and IL-6 mRNA in the jejunum, ileum and colon tissues in the treatment groups and concluded that yeast cell wall derivates may lower the inflammatory response, protecting the intestinal tissue.…”
Section: Discussionsupporting
confidence: 91%
“…To determine if the immune‐modulating effects of arabinoxylan can be explained by binding to PRRs, the activation of TLR2, 4, 5, and Dectin‐1 by arabinoxylan was studied. All these PRRs either recognize carbohydrate groups or are implicated in the recognition of dietary fibers . Reporter cell lines with either human TLR2, TLR4, TLR5, Dectin‐1A, or Dectin‐1B receptors were stimulated with arabinoxylan fibers.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that live yeast stabilizes rumen pH [ 6 , 7 ], and the number of anaerobic cellulolytic bacteria [ 8 , 9 ]. In addition to having nutritional value, there is evidence that yeast probiotics and their components, such as mannan-oligosaccharides (MOS), can adhere to enteric pathogens including Campylobacter jejuni [ 10 ], Escherichia coli serotypes (O2 and O88) [ 11 ], and Salmonella [ 12 , 13 ], thereby reducing their ability to attach to and invade host cells [ 14 ]. Given these properties, it is possible that dietary supplementation with yeast probiotics and/or their components may help protect calves that are vulnerable to Johne’s disease (JD).…”
Section: Introductionmentioning
confidence: 99%